Comparison of the effectiveness between c-mac d-blade and glidescope for tracheal intubation in patients with cervical spine immobilisation simulated by a semi-rigid collar - Che Wil, Farah Fatmawati (2015)

(untitled)
Objective: Among the technique for cervical spine immobilisation is putting on semi-rigid collar but it renders difficult tracheal intubation. In this study, our aim is to compare the effectiveness of two available videolaryngoscopes meant for difficult intubation C-MAC D-Blade (DB) and GlideScope (GS). In terms of improvement of glottic view, time for successful intubation and haemodynamic changes on patients with a semi-rigid cervical collar. Methodology: This was a prospective, single-blinded, controlled trial with eighty patients scheduled for elective surgery under general anaesthesia. They were selected during premedication round with ASA I-II without any features of difficult intubation. They were randomized equally into two groups, 40 patients each group according to the studied videolaryngoscopes. After induction of general anaesthesia the semi-rigid collar was placed and repeated laryngoscopy was performed using conventional direct Macintosh laryngoscope, C-MAC D-Blade or GlideScope according to randomisation groups before patients were intubated with GliteRite styleted endotracheal tube. Glottic view was scored using Cormack Lehane (CL) and Percentage of Glottic Opening (POGO) scores with Macintoch and respective videolaryngoscope and time for successful intubation were recorded. All patients were successfully intubated by one operator experienced in the use of each laryngoscopes. Patient’s blood pressure, MAP and heart rate were recorded as a baseline value, post intubation at 1, 3, 5 and 10 minutes. Results: Both videolaryngoscopes showed significantly better Cormack Lehane grade and POGO scores than direct laryngoscope by Macintosh (DL). Majority of glottic view by DL were CL III and IV in both group. It was significantly reduced with the C-MAC D-Blade (DB), 40 patients (100%) had CL I and GlideScope (GS), 30 patients (75%) and 9 patients (22.5%), had CL I and CL II respectively. Only 1 patient had CL III by GlideScope and none had CL IV. Time to best achievable glottic view was significantly better in DB group with mean (SD) 11.68 (3.24) seconds vs 14.69 (5.59) seconds in GS group, p<0.001. Successful intubation time was significantly shorter in DB 37.57 (10.81) seconds than GS 53.03 (14.45) seconds, p<0.001. There were no significant changes in the baseline hemodynamic parameters (SBP, DBP, MAP and HR) and after intubation except reduced SBP in GS at 5 minutes post intubation. However there were significantly reduced SBP, DBP and MAP in both DB and GS between pre-intubation and post intubation. Hence no difference on incidence of complication in both groups. Conclusions: Compared to direct Macintosh laryngoscopy, both C-MAC D-Blade and GlideScope resulted in an improved view of glottic opening with successful intubation in all patients. The C-MAC D-Blade showed superior performance than GlideScope in this group of patient with semi-rigid collar applied during intubation on improvement of CL score and shorter duration for intubation. DB may serve as device of choice for intubation in difficult situation but further study needed to confirm these findings.